Spatiotemporal Characteristics of Land Ecological Security and Rural Revitalization Coordination in Guangxi Zhuang Autonomous Region - Bing Li; Xing Zhou; Haiping Chen (Shuitu baochi tongbao, 2023)
[Objective] The level and coordination of spatial and temporal characteristics of land ecological security and rural revitalization and development in Guangxi Zhuang Autonomous Region from 2010 to 2020 were studied in order to promote land ecological security protection and to improve the level of rural revitalization and development, resulting in coordinated development of both factors. [Methods] We analyzed data from 14 cities in the Guangxi Zhuang Autonomous Region to build an index system. The comprehensive measurement level and coupling coordination model were used for analysis. [Results] ① The level of land ecological security increased over time. ② The overall development level of rural revitalization initially declined and then increased, but the development level of each city was different. ③ The coordination degree changed in the form of “uneven rise and fall”. The level of coordination degree was distributed in a trend of gradual increase from east and west to the central region, from inland to the coast, and from the central region to the north. The development pattern was “low from east to west, high from south to north”. ④ Different development modes and development centers should be adopted according to the regional types of the 14 cities. [Conclusion] Coordinated development of land ecological security and rural revitalization in the Guangxi Zhuang Autonomous Region has not been stable. In the future, we should strengthen the integrated development of land ecological security and rural revitalization in low-level coordination areas, and combine them with policies, people’s livelihood, and development promotion measures to improve the coordination level between the two factors. At the same time, we should stabilize the coordinated development between the two factors in mature areas to prevent loss of existing coordinated development.